Effect of Oxide’s Thermophysical Properties on 2205 Duplex Stainless Steels ATIG Welds - Rachid Djoudjou; Kamel Touileb; Elawady Attia; Abousoufiane Ouis; Abdeljlil Chihaoui Hedhibi; Hany S. Abdo; Ibrahim AlBaijan (Crystals)
Duplex stainless-steel grade 2205 (2205 DSS) is the most widely used of the current duplex materials. The duplex steel alloy is characterized by high strength and high corrosion resistance through enhancing nitrogen and molybdenum contents. The activated tungsten inert gas (ATIG) welding technique uses the same equipment as tungsten inert gas (TIG), but prior to the welding operation, a thin layer of flux is deposited. Activation fluxes are known to influence the shape and energy characteristics of the arc. They promote the change in shapes and dimensions of the welds, namely, increasing the depth and narrowing the weld width. This work is dedicated to investigate the influence of the thermophysical properties of individual metal oxide fluxes on 2205 DSS welding morphology. It helps also to identify the recommended flux properties in order to perform full penetrated ATIG welds. Thirteen kinds of oxides (SiO2, TiO2, Fe2O3, Cr2O3, ZnO, Mn2O3, V2O5, MoO3, Co3O4, SrO, ZrO2, CaO, and MgO) have been tested and three current intensity levels (120, 150 and 180 A) have been considered. The results showed that the main input factors affecting the weld depth (D) were the welding current intensity with a contribution of up to 53.36%, followed by the oxides enthalpy energy with 15.05% and then by the difference between the oxides and the base metal of 2205 DSS (BM 2205 DSS) melting points with a contribution of 9.71% of the data variance. The conditions on individual oxides’ thermophysical properties to achieve full penetrated weld beads have been also revealed.